Power Quality Improvement Using Three Phase Four Wire Unified Power Quality Conditioner - B.Thanusha, G.Sujatha, P.Mamta (International Journal of Advanced Science and Technology, 2020)
This paper presents the controlstrategy for selective compensation of power quality problems through a three phase four wire unified power quality conditioner. UPQC includes shunt Active power filter and series Active power filter. There two filters consists of voltage source inverter (VSI) separately and are connected by a common DC link. Here the control technique used for both filters is synchronous reference frame (SRF). This whole project is validated through simulations using MATLAB software. Keywords: Unified Power Quality Conditioner, voltage source inverter, shunt and series active power filter, power quality